Novel immunoenzymatic assay for identification of coagulase- and protein A-negative Staphylococcus aureus strains. - Guzmàn, C A (1992)
A purified monoclonal antibody (MAb) which specifically reacts with Staphylococcus aureus glucosaminidase was obtained. This MAb was utilized to develop an immunoenzymatic assay for the identification of S. aureus strains. The sensitivity of this assay, based on the simultaneous detection of S. aureus glucosaminidase and protein A, was evaluated by analyzing a total of 196 strains, 26 of which did not exhibit one or more of the following properties: protein A, clumping factor, and staphylocoagulase. All strains yielded positive results by the MAb-based immunoenzymatic test. The assay's ability to differentiate between S. aureus and other staphylococci was then analyzed by testing a total of 277 non-S. aureus strains that yielded negative results. Our data demonstrate that this immunoenzymatic assay can be used as a single S. aureus identification criterion, particularly useful for those strains negative for clumping factor, staphylocoagulase, or protein A.